(x+6)(x+8) = 0
x = -6 or x = -8
I'm just wondering, does the equation happen to be 2x^2 + 14x + 48? That would make more sense with the answer I got.
Answer:
92.5
Step-by-step explanation:
Lets say, first number = x
Second number = 3x+7
Total = 49
(x)+(3x+7)= 49
4x+7 = 49
4x = 42
x = 42/4
x= 10.5
x= 10.5
3x+7 = 3(10.5)+7 = 92.5
Hope this helps!!
Answer:
theres is not table shown
Step-by-step explanation:
Answer:
x>-4
Step-by-step explanation:
-3x<12
x>-4
Answer:
m = -10 + 5p
Step-by-step explanation:
5p − m = 10
subtract 5p from both sides:
5p − m - 5p = 10 - 5p
simplifiy:
-m = 10 - 5p
divide -1 to both sides
m = -10 + 5p
m = -10 + 5p
===========